PELAKSANAAN HUBUNGAN MASYARAKAT DALAM MEMBANGUNNETWORKING DI SMK NEGERI 1 SURABAYA - ARISTA NURCAHYANI, NOVI (Inspirasi Manajemen Pendidikan, 2016)
This study uses a qualitative approach and case study design. The technique of collecting data uses interviews,observation and documentation methods. Data analysis applies data reduction, data presentation, and data verification.Checking the validity of the data is done with credibility, transferability, dependability, and conformability.Research results show that: (1) Implementation of public relations at SMK Negeri 1 Surabaya is conductedafter the previous planning process, in the implementation of public relations of all school parts involved ranging fromschool principals, teachers, human relation manager and school committees. Public relations in vocational schoolcollaborates with various relationships; (2) the media used in the implementation of public relations at the schoolincludes printed and electronic media; using internal media and external media in the implementation of public relationsat the school. (3) The work done in building internal networking at the school includes the coordination betweeninternal stakeholders by using media ( coordination ) and use of communication in its implementation; (4) the workdone in constructing external networking in schools is to form a team of public relations in establishing cooperation,after that, it carried out assessments of cooperation by analyzing the information in advance with relevant partners todo the cooperation, done bysigning cooperation agreement or contract with a partner related.Keywords: Implementation of community relations, the media in the implementation of public relations, efforts to buildnetworking internally and efforts to build networking externally.